Review of Schizosairhynchus (Phthiraptera: Ischnocera: Philopteridae: Brueelia-complex), with descriptions of four new species - Gustafsson, Daniel R. (Zootaxa, 2026)
Four new species of the head louse genus Schizosairhynchus Gustafsson & Bush, 2017 are described and illustrated based on specimens from Australo-Papuan starlings (Sturnidae). They are: Schizosairhynchus anahitae sp. nov. ex Mino anais orientalis (Schlegel, 1871); Schizosairhynchus bilobus sp. nov. ex Aplonis panayensis strigatus (Horsfield, 1821) and Aplonis panayensis panayensis (Scopoli, 1786); Schizosairhynchus guadalcanalensis sp. nov. ex Mino kreffti (Sclater, 1869) and Schizosairhynchus sarcoplestes sp. nov. ex Sarcops calvus melanonotus Ogilvie-Grant, 1906. The species Schizosairhynchus philippensis (Tandan & Kumar, 1969), Schizosairhynchus erysichthoni Gustafsson & Bush, 2017 and Schizosairhynchus minovenator Gustafsson & Bush, 2017 are reillustrated for comparison. A key to all known species of Schizosairhynchus is given. Also, a list of species of lice belonging to head ecomorph genera parasitizing species of Sturnidae is provided.